PENGARUH KEPEMIMPINAN, KOMUNIKASI, KONFLIK TERHADAP MOTIVASI DAN DAMPAKNYA PADA KINERJA PEGAWAI DINAS PERINDUSTRIAN DAN PERDAGANGAN ACEH - Elisa Diana; Nasir Nasir; Said Musnadi (FEB - Unsyiah, 2018)
The purpose of this research is to know / analyze: (1) the influence of leadership on employee motivation, (2) the effect of communication on employee motivation, (3) the influence of conflict on employee motivation, (4) the influence of leadership on employee performance, (5) the effect of communication on employee performance, (6) the effect of conflict on employee performance, (7) the influence of motivation on employee performance, (8) the indirect influence of leadership on employee performance through employee work motivation, (9) the indirect influence of communication on the performance of employees through employee work motivation, (10) the indirect effect of conflict on the performance of employees through employee work motivation. This research was conducted at the Department of Industry and Trade of Aceh. As for the object of this research is leadership, communication, conflict and work motivation and employee performance, with the number of respondents as many as 130 people. The result of this research shows that leadership influence to employee work motivation, communication also influence to employee work motivation, conflict between employee have influence to work motivation, work motivation possessed by employee have influence to improvement of employee performance, leadership owned by employee have an effect on performance employee, communication influence to employee performance, then conflict influence to employee performance, there is indirect influence of leadership to employee performance through employee work motivation, there is indirect influence of communication to employee performance through employee work motivation, there is indirect influence of conflict to officer performance through employee work motivation